1971
DOI: 10.1088/0029-5515/11/3/009
|View full text |Cite
|
Sign up to set email alerts
|

On magnetohydrodynamic waves in inhomogeneous magnetic fields

Abstract: The theoretical analysis of the propagation of magnetohydrodynamic waves in a cylindrical plasma immersed in a steady inhomogeneous magnetic field is here undertaken by assuming a model field of two constant field regions joined by the field B⃗ = A∇(l/r). We thus consider ‘beach’ and ‘cliff’ magnetic field configurations. The general solution of the coldplasma equations in the central (inhomogeneous field) region must be found numerically, but in the low-frequency case analytic solutions are obtained. The wave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1972
1972
1983
1983

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…In the presence of Mg2+ alone the methylation of tRNA by crude extracts from mammalian tissues produces mainly methylated guanosine derivatives, but addition of polyamines or NH4+ allows the formation of 1-methyladenosine and 5-methylcytidine (Leboy, 1971;Pegg, 1972a,b;Leboy & Piester, 1973). These latter products are formed in the 'T#C loop' and the 'extra arm' region, which may be oriented in the tertiary structure of the tRNA (Levitt, 1969;Cramer, 1971;Kim etal., 1973) such that methylation occurs only when the tRNA structure is altered.…”
Section: Product Of Methylationmentioning
confidence: 99%
“…In the presence of Mg2+ alone the methylation of tRNA by crude extracts from mammalian tissues produces mainly methylated guanosine derivatives, but addition of polyamines or NH4+ allows the formation of 1-methyladenosine and 5-methylcytidine (Leboy, 1971;Pegg, 1972a,b;Leboy & Piester, 1973). These latter products are formed in the 'T#C loop' and the 'extra arm' region, which may be oriented in the tertiary structure of the tRNA (Levitt, 1969;Cramer, 1971;Kim etal., 1973) such that methylation occurs only when the tRNA structure is altered.…”
Section: Product Of Methylationmentioning
confidence: 99%
“…In 1964 Rosset et al discovered ribosomal5 S RNA [ 11, which was subsequently sequenced from a number of prokaryotic [2-41 and eukaryotic organisms [S-7]. Comparison of the sequence of KB cell 5 S RNA [5] with that of E. coli [2] lead Forget and Weissman [ 51 to propose that the common 5 S RNA sequence CGAAC would interact with the common GT\kCPu (loop IV) sequence of tRNA [8,9]. More recent data has shown that all 5 S RNAs contain the oligonucleotide or one similar to CGAAC [2-7, lo] .…”
Section: Introductionmentioning
confidence: 99%
“…For z > 130 cm, fast waves typically have parallel wavelengths a few times the scale length, so the eikonal approximation must be examined more carefully. Cramer [10] studied propagation of fast and slow waves along a model inhomogeneous magnetic field. Cramer's results on fast-wave propagation show that little reflection occurs until the scale length is less than about 50% of the parallel wavelength.…”
Section: Central Regionmentioning
confidence: 99%
“…To assess the validity of the eikonal approximation for the parallel variation of slow waves in TMX, we turn again to the work of Cramer [10]. He found little ( < 20%) reflection of slow waves unless the scale length was less than about 20% of the wavelength.…”
Section: Resonance Regionmentioning
confidence: 99%
See 1 more Smart Citation